Two-Scale Multimodal Medical Image Fusion Based on Structure Preservation - Liu, Shuaiqi; Wang, Mingwang; Yin, Lu; Sun, Xiuming; Zhang, Yu-Dong; Zhao, Jie (Frontiers in Computational Neuroscience, 2022)
Medical image fusion has an indispensable value in the medical field. Taking advantage of structure-preserving filter and deep learning, a structure preservation-based two-scale multimodal medical image fusion algorithm is proposed. First, we used a two-scale decomposition method to decompose source images into base layer components and detail layer components. Second, we adopted a fusion method based on the iterative joint bilateral filter to fuse the base layer components. Third, a convolutional neural network and local similarity of images are used to fuse the components of the detail layer. At the last, the final fused result is got by using two-scale image reconstruction. The contrast experiments display that our algorithm has better fusion results than the state-of-the-art medical image fusion algorithms.